Fuel management operations planning in fire management: A bilevel optimisation approach. (May 2021) - Liberatore, Federico; León, Javier; Hearne, John; Vitoriano, Begoña
Highlights: Elevated fuel loads represent a wildfire hazard in a landscape. Reducing fuel load is a mitigation strategy that decreases the impact of wildfires. A problem for fuel treatment planning is presented, formulated, and solved. The model identifies areas to treat to minimise the impact of the worst-case wildfire. Method tested on random instances and on a dataset of reserve in Andalusia, Spain. Abstract: Elevated fuel loads represent a wildfire hazard in a landscape. Reducing fuel load is one mitigation strategy commonly employed to decrease the severity and impact of wildfires. The planning of such fuel management operations, however, represents a complicated decision problem, which includes multiple sources of uncertainty. In this paper, a problem for fuel treatment planning is presented, formulated, and solved. The optimisation model identifies the best subset of units in the landscape to be treated to minimise the impact of the worst-case wildfire. Due to its size, which would make it intractable for realistic instances, an ad hoc exact solution algorithm has been devised. Extensive computational testing on randomly generated instances illustrates that the proposed approach is very successful at solving the problem. Finally, the algorithm is applied to a case study on a landscape in Andalusia, Spain, which shows the capabilities of the proposed approach in addressing a real-world problem.